2022
DOI: 10.3390/jof8040368
|View full text |Cite
|
Sign up to set email alerts
|

Substrates of the MAPK Slt2: Shaping Yeast Cell Integrity

Abstract: The cell wall integrity (CWI) MAPK pathway of budding yeast Saccharomyces cerevisiae is specialized in responding to cell wall damage, but ongoing research shows that it participates in many other stressful conditions, suggesting that it has functional diversity. The output of this pathway is mainly driven by the activity of the MAPK Slt2, which regulates important processes for yeast physiology such as fine-tuning of signaling through the CWI and other pathways, transcriptional activation in response to cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 155 publications
0
17
0
Order By: Relevance
“…MAPK pathway is essential for the formation and regulation of fungal cell walls [ 57 ]. Further analysis of DEGs showed that nine DEGs were mapped in the MAPK signaling pathway—yeast KEGG pathway, including six up-regulated DEGs ( fks2 , rsp5 , stt4 , bmh1,2 , ptp2,3 , mkk1,2 ) and three down-regulated DEGs ( yck1,2 , sln1 , ctt1 ).…”
Section: Resultsmentioning
confidence: 99%
“…MAPK pathway is essential for the formation and regulation of fungal cell walls [ 57 ]. Further analysis of DEGs showed that nine DEGs were mapped in the MAPK signaling pathway—yeast KEGG pathway, including six up-regulated DEGs ( fks2 , rsp5 , stt4 , bmh1,2 , ptp2,3 , mkk1,2 ) and three down-regulated DEGs ( yck1,2 , sln1 , ctt1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mpk1 belongs to the cell wall integrity signalling pathway, which is responsible for the maintenance and biosynthesis of the cell wall and has been linked to various other cellular processes such as cell division, autophagy, proteasome assembly, and plasma membrane homeostasis ( 32 , 33 ). As Mpk1 contributes to stress-induced Shp1 phosphorylation, Shp1 could play a role downstream of this kinase.…”
Section: Discussionmentioning
confidence: 99%
“…In oomycetes and fungi, MAPK cascades also play a key role in the development and plant infection (Jiang et al, 2017;Gonzalez-Rubio et al, 2019). Sporangium formation is severely diminished in PsMPK1-silenced mutants (Li et al, 2014).…”
Section: Pathways Involved In Sporangium Formation and Cleavagementioning
confidence: 99%